Prophylactic antibiotic therapy for preventing poststroke infection - Schwarz, Stefan (Neurotherapeutics, 2016)
Infections, in particular pneumonia, are common complications in patients with acute stroke and are associated with a less favorable neurologic and functional outcome. Patients with severe stroke and dysphagia are at highest risk of infection. Experimental and clinical data suggest stroke-induced immunodeficiency as a major factor contributing to the high incidence of infection after stroke. Preclinical studies support the potential benefit of preventive antibiotic therapy in acute stroke for lowering the incidence of infection and improving clinical outcome. Several smaller clinical trials on preventive antibiotic therapy in patients with stroke conducted during the last 10 years yielded inconclusive results. Recently, 2 large, open-label, controlled trials failed to demonstrate an improved clinical outcome after preventive antibiotic therapy in patients with acute stroke treated in specialized stroke units. In the “Preventive Antibiotics in Stroke Study”, antibiotic therapy lowered the rate of infection but did not influence outcome. In the STROKE-INF study, performed in patients with dysphagia after stroke, antibiotic therapy did not lower the incidence of pneumonia and had no prognostic significance. At present, preventive antibiotic therapy cannot be recommended as a therapeutic option for acute stroke.
Gesehen am 17.07.2019